Experimental modelling of spray deflection influence on planing craft performance in calm water and waves. (May 2020) - Wielgosz, Chiara; Rosén, Anders; Datla, Raju; Chung, Uihoon; Danielsson, Jonas
This study explores the prospects of using scaled model experiments for capturing the influence of a novel spray deflection concept on planing craft performance in calm water and in waves. An experimental setup with a towed planing craft model is designed and systematic experiments are performed, first with a bare hull model and then with the same model equipped with spray deflectors. Measured trim, sinkage and resistance in calm water and accelerations and resistance in waves are presented. The results, as well as various aspects of the experimental setup and the spray phenomenon, are discussed. The experimental results indicate that the studied spray deflector concept can have positive effects by lowering the resistance as well as the acceleration in waves. The detailed tailoring of the deflectors is concluded to be crucial. The developed experimental setup is concluded to give consistent results that capture the influence of the spray deflection details on the craft resistance and responses and is concluded to be useful for further research as well as for design purposes.